2019
DOI: 10.3339/jkspn.2019.23.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Steroid Resistant Nephrotic Syndrome

Abstract: Steroid-resistant nephrotic syndrome (SRNS) has long been a challenge for clinicians due to its poor responsiveness to immunosuppressants, and rapid progression to end-stage renal disease. Identifying a monogenic cause for SRNS may lead to a better understanding of podocyte structure and function in the glomerular filtration barrier. This review focuses on genes associated with slit diaphragm, actin cytoskeleton, transcription factors, nucleus, glomerular basement membrane, mitochondria, and other proteins tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…Additionally, MYH9 gene deletion was observed to affect the repopulation ability of haematopoietic stem/progenitor cells while increasing apoptosis, implying its involvement in organismal haematopoiesis (31). Furthermore, proteomic analysis revealed the significant potential of MYH9 in early prediction of GCR childhood nephrotic syndrome, positioning it as a potential candidate biomarker for evaluating glucocorticoid efficacy (32)(33)(34). Our proteomics study also found that the difference in MYH9 protein levels between the GCS and GCR groups was statistically significant.…”
Section: Discussionsupporting
confidence: 59%
“…Additionally, MYH9 gene deletion was observed to affect the repopulation ability of haematopoietic stem/progenitor cells while increasing apoptosis, implying its involvement in organismal haematopoiesis (31). Furthermore, proteomic analysis revealed the significant potential of MYH9 in early prediction of GCR childhood nephrotic syndrome, positioning it as a potential candidate biomarker for evaluating glucocorticoid efficacy (32)(33)(34). Our proteomics study also found that the difference in MYH9 protein levels between the GCS and GCR groups was statistically significant.…”
Section: Discussionsupporting
confidence: 59%
“…Initially, Kestilä et al identified NPHS1 as the causative gene for the Finnish form of congenital nephrotic syndrome [14]. Over 250 mutations within the NPHS1 gene have already been implicated in a variety of kidney disorders [15].…”
Section: Introductionmentioning
confidence: 99%